Digital Educational Materials for journalist on disaster risk management. Advances and limitations - Manotas Salcedo, Edna Margarita; Barrios, Marta Milena; Arroyave, Jesus; Vega, Lina; García, Josslyn (Revista Española de Comunicación en Salud, 2019)
This article carried out a content analysis on 28 digital educational materials published between 2012 and 2018, to train Latin American journalists in Disaster Risk Management (DRM). The aim of the study was to establish whether the focus of these pedagogical resources was consistent with the guidelines of the international agencies for the education of the reporters. This, by generating a change in the way they are covering this issue. The main goal of this courses should be that the public journalistic discourse changes their traditional centrality on disasters and their attention to emergencies, as well as to start communicating prevention. The results of the analysis identified progress and limitations in the construction of the resources, both in what concerns their pedagogical relevance and in the inclusion of central themes for DRM. Based on the findings, reflections are offered on how these resources could be improved to fulfill their objective of contributing to a collective mobilization that favors prospective risk management and strengthens social development.